Trait association and magnitude of direct and indirect effects on yield in sorghum(Sorghum bicolor L. Moench) genotypes - Gorajana, Nalini Naidu; Gupta, Praveen Kumar; M Elangovan; V, Narsimha Reddy; Gogada, Raghu (Journal of Cereal Research, 2024)
The present investigation was carried out with 65 accessions of sorghum genotypes along with 3 checks to estimates the association among different traits and magnitude of direct and indirect effects on grain yield per plant. Results of correlation analysis pointed out highly significant and positive association at both phenotypic and genotypic levels by dry panicle weight (rg=0.7, rp=0.698), leaf width (rg=0.657, rp=0.607) followed by moderately significant and positive association by dry matter production (rg=0.54, rp=0.522) and fodder yield (rg=0.535, rp=0.518) with the dependent character grain yield per plant. The magnitudes of genotypic correlation were found higher than the phenotypic correlation. Partitioning of yield and its component traits at phenotypic levels into direct and indirect contribution of the traits exhibited highest positive direct effects on grain yield per plant were dry panicle weight (Ppi=0.697) followed by fodder yield (Ppi =0.053) and 100-seed weight (Ppi =0.028). Hence, these parameters may be considered as selection indices in sorghum breeding programmes.